THE INFLUENCE OF GOOD HOSPITAL GOVERNANCE IMPLEMENTATION ON HOSPITAL PERFORMANCE WITH POSITIVE ORGANIZATIONAL CULTURE AS A MEDIATING VARIABLE - Riyanda; Farida Yulianty (RADJA PUBLIKA, 2025)
This study examines the influence of Good Hospital Governance (GHG) on the performance of Bhayangkara Hospital Pontianak, with positive organizational culture serving as a mediating variable. The research adopts a literature review approach, synthesizing findings from national and international studies that explore the interconnectedness between governance, organizational culture, and healthcare performance. The analysis reveals that effective implementation of GHG characterized by accountability, transparency, fairness, and ethical integrity plays a crucial role in improving hospital outcomes, including service quality, operational efficiency, and patient satisfaction. However, the effectiveness of governance depends largely on the presence of a positive organizational culture that encourages collaboration, open communication, and shared responsibility among healthcare professionals. Such a culture acts as a bridge that transforms governance structures from formal regulations into behavioral norms, fostering motivation and innovation across the organization. Within the context of Bhayangkara Hospital Pontianak, the findings highlight that the integration of disciplined administrative systems with a compassionate, patient-centered culture enhances overall institutional performance.